RECORD OF THE OCEANIC SQUID SYMPLECTOTEUtTHIS OUALANIENSIS (LESSON) CAUGHT OFF MANGROL, SAURASHTRA COAST - Raje, S G; savaria, Y D (Indian Journal of Fisheries, 2011)
A female specimen of the oceanic squid Symplectoteuthis otialaniensis (Lesson) measuring 434 Imm in mantle length and 2.460 kg in weight caught by drift net off Mangrol is: reported, giving the monphometrlc moasurements. A single female specimen of the oceanic squid Symplectoteuthis oulaniensis (Lesson) was caught in a drift gill net (150 mm mesh) off Mangrol, from an area 80 m in depth, it Saurashtra coast on February 6, 1986 (Fig. 1). The specimen measured 434 mm in dorsal mantle length and 2.460 kg in weight. Both the tentacles had been mutUated. The gonad was in maturing condition and the gut was full with thoroughly macerated and pulpy food.